THE DETERMINATION OF THE PARAMETERS OF THE NOMINAL MODE OF PASSENGER LOCOMOTIVES FOR THE RAILWAYS OF UKRAINE - Hetman, H. K.; Arpul, S. V. (Science and Transport Progress, 2008)
The basic results of determination of rational parameters of the nominal regime of passenger electric locomotives with an asynchronous hauling drive for railways of Ukraine are presented.